2017
DOI: 10.1111/tbj.12947
|View full text |Cite
|
Sign up to set email alerts
|

Nipple-sparing mastectomy as treatment for patients with ductal carcinoma in situ: A 10-year follow-up study

Abstract: The objective was to determine the 10-year oncological safety of nipple-sparing mastectomy (NSM) in patients diagnosed with ductal carcinoma in situ (DCIS). The use of NSM preserves the nipple-areola complex (NAC). As residual fibroglandular breast tissue can remain behind the spared NAC, its use for patient with breast cancer is controversial. The oncologic outcomes and complication rates after performing NSM compared to other techniques are still under debate and a concern when treating patients with breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
3
12
0
2
Order By: Relevance
“…The average rate of local recurrence was in line with our results which detected a total local relapse rate (NAC and skin) of 4.9%. The overall complications rate (early and late) of this study is comparable with those reported in the literature [15][16][17] and the reported risk of recurrence is low [18]. According to Stolier et al, there are not terminal duct-lobular units inside the nipple in 91% of cases and only in 9% of cases the duct-lobular units are few and located at the base of the nipple [19].…”
Section: Discussionsupporting
confidence: 84%
“…The average rate of local recurrence was in line with our results which detected a total local relapse rate (NAC and skin) of 4.9%. The overall complications rate (early and late) of this study is comparable with those reported in the literature [15][16][17] and the reported risk of recurrence is low [18]. According to Stolier et al, there are not terminal duct-lobular units inside the nipple in 91% of cases and only in 9% of cases the duct-lobular units are few and located at the base of the nipple [19].…”
Section: Discussionsupporting
confidence: 84%
“…Nipple-sparing mastectomy (NSM) was initially reserved for the prophylactic treatment of women with a high risk of developing breast cancer [10]. However, NSM has been increasingly used therapeutically for breast cancer where the nipple-areolar complex is not involved [11][12][13][14]. One of the most important challenges of nipple-sparing mastectomy is achieving adequate exposure to performing precise dissection in areas that are remote from the skin incision [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although in this particular patient, the FS did not alter the next steps of the surgical procedure, a false positive FS result (in particular with an invasive cancer diagnosis) could dramatically affect surgical decisions. As an example, a DCIS diagnosis may entail "radical" treatments including mastectomy, nipple-sparing mastectomy [20,21] or breast-conserving therapy followed by adjuvant radiation in most cases. Finally, in cases of "upstaging" from DCIS to invasive ductal carcinoma [22], the false diagnosis could erroneously alter therapeutic options.…”
Section: Discussionmentioning
confidence: 99%